Chemical Treatment for Mixed Wastewater in Small Communities in Egypt - Reem Elhalafawy; Badr E. Hegazy; Rehab El Hefny; Ahmed M. Hassanain (Archives of Current Research International, 2017)
Aims: Applying advanced oxidation process, by Fenton’s reaction, to treat mixed wastewater. The study focused on treatment of domestic sewage mixed with industrial wastewater generated from sugar industry. Study Design: The research focused on studying the optimum dose of hydrogen peroxide and the retention time to treat influent fresh mixed wastewater samples, which include domestic sewage and industrial wastewater. The used fresh mixed wastewater samples were collected from the influent of El-Hawamdya wastewater treatment plant. El-Hawamdya wastewater treatment plant is located in Abu-Seir village in Giza, Egypt. Methodology: The plant contains units of primary sedimentation tanks, trickling filter and final settling tanks and chlorine dose often added before disposal of the treated wastewater. The plant daily capacity is about 20,000 m3/d. The input wastewater includes about 76% of domestic sewage and 22% of sugar industry’s wastewater plus 2% from small industries. The applied experiments were determined in order to achieve, both, efficiency and economical benefit. Results: Based on the experimental work program executed in this research, and limited to the tested materials and testing procedures, it has been found that the overall optimum dose for H2O2 is 1.5 mg/l with a 20 minutes retention time. Conclusion: It has been concluded that the chemical treatment, by Fenton reaction, can be used for treatment of fresh raw mixed wastewater, under the circumstances of the study, with acceptable efficiency and suitable cost.